Corrosion behavior of crystalline silicon solar cells. (March 2017) - Xiong, Huaping; Gan, Chuanhai; Yang, Xiaobing; Hu, Zhigang; Niu, Haiyan; Li, Jianfeng; Si, Jianfang; Xing, Pengfei; Luo, Xuetao
Abstract: Corrosion behavior of crystalline silicon (C-Si) solar cells was investigated. For this purpose, three groups of cells were conducted with three kinds of aging test which cells setting in indoor environment (25 °C, 45% RH, 0– 2 months), cells immersing in moisture atmosphere (25 °C, 85% RH, 0– 240 h) and cells immersing in acetic acid atmosphere (25 °C, 85% RH, 0– 240 h). Subsequently the microstructure characteristic of the alumina paste layer (APL), rear electrode and soldered connection of cells and the corrosion production during aging test were analyzed and compared. The results show that the smooth oxide coating and looser structure were found in the APL of cell after aging test. In addition the discoloration and elements diffusion were found on the rear electrode. And the corrosion region expanded gradually from the edge to the center of soldered connection along the interface between Ag electrode and Sn37 Pb alloy. Thereafter, a model was put forward to try to explain the degradation mechanism of traditional photovoltaic (PV) modules during damp-heat (DH) test based on corrosion behavior of C-Si cells in this experiment. Highlights: Corrosion would bring smooth oxide coating and looser structure to Al layer. Corrosion would bring discoloration and oxide coating to rear electrode. Corrosion region will expand from the edge to the center of soldered joints. Degradation rate of traditional modules was low before 2000 h, and then increased.